Karta Povi︠e︡net︠s︡koĭ bukhta Onezhskago ozera sʺ Orov-guboi︠u︡. Sostavlena po opiseĭ 1882-84 g.g. / Izdana Gidrograficheskimʺ Departmentomʺ Morskago Ministerstva vʺ 1885 godu - Russia. Gidrograficheskīĭ departament (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1885)
Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; Map of Povenets Bay with Orovguba Bay.; Pulkovo meridian.; "Povi︠e︡net︠s︡kīĭ Reĭdʺ" -- across top margin.; "Masshtabʺ 300 sazh. vʺ di︠u︡ĭmi︠e︡ (1/25200)." [Scale 300 sazhens in 1 inch (1/25200)].; "No. 175" -- handwritten bottom right margin Grayscale; 1:25,200